Self-management of overactive bladder at home using transcutaneous tibial nerve stimulation: a qualitative study of women's experiences - Ciara M. E. Daly; Lynette Loi; Jo Booth; Dalia Saidan; Karen Guerrero; Veenu Tyagi (BMC, 2021)
Abstract Background Transcutaneous tibial nerve stimulation (TTNS) has been used to treat overactive bladder (OAB), however patient experiences and views of this treatment are lacking. The aim of this study was to explore women's experiences of OAB and TTNS treatment and the perceived factors influencing participation and adherence. Methods Semi-structured, individual interviews conducted as part of a mixed-methods, randomised, feasibility trial of self-managed versus HCP-led TTNS. Interviews were audio recorded and transcribed verbatim. Reflexive thematic analysis was undertaken using Booth et al. (Neurourol Urodynam. 2017;37:528-41) approach. Results 16 women were interviewed, 8 self-managing TTNS at home and 8 receiving TTNS in twice-weekly hospital clinic appointments. Women self-managing OAB considered TTNS easy to administer, flexible and favourably 'convenient', especially when the participant was bound by work and other life commitments. In contrast to OAB symptoms 'dominating life', self-managing bladder treatment was empowering and fitted around home life demands. Flexibility and control engendered by self-management, facilitated women's willingness to participate in TTNS. Women attending a hospital clinic for TTNS enjoyed the social aspects but found the routine appointments constrained their lives. Motivation to continue TTNS in the longer term was dependent on perception of benefit. Conclusions This study provides novel insights into women's experiences of self-managing their OAB using TTNS compared to HCP-led management in the clinical setting. It highlights positive experiences self-managing TTNS at home and a willingness to continue in the longer term, facilitated by ease of use and convenience. Trial Registration 1/11/2018: ClinicalTrials.gov Identifier: NCT03727711.